EXPLORING PRE-SERVICE TEACHERS' EXPERIENCES WITH DIGITAL MULTIMODAL COMPOSING IN NARRATIVE STORYTELLING: MENGEKSPLORASI PENGALAMAN CALON GURU DENGAN PENYUSUNAN MULTIMODAL DIGITAL DALAM PENCERITAAN NARATIF - Sadikin, Irma Savitri; Santosa, Imam; Fadli, Muhammad Rijal; Fatonah, Khusnul; Ulum, Muhamad Bahrul (ELTIN Journal, 2025)
In the 21st century, digital competency is a fundamental requirement for language instruction, necessitating the integration of technology into teacher training programs. This study investigates four pre-service teachers’ experiences in designing digital narrative videos using the Digital Multimodal Composing (DMC) framework. Adopting a narrative inquiry approach, data were gathered through reflective diaries and semi-structured interviews to explore how participants engaged with the critical, creative, and technical domains of multimodal composition. Findings indicate that pre-service teachers initially faced challenges in conceptualizing multimodal elements but gradually developed confidence in integrating text, visuals, and audio to enhance their instructional materials. They critically analyzed multimodal texts, structured their narrative-based lessons for greater engagement, and refined their technical proficiency with digital tools. Peer discussions and online tutorials played a significant role in helping them navigate the complexities of multimodal composing, fostering collaborative learning and iterative refinement. This study emphasizes the role of DMC in preparing pre-service teachers for technology-enhanced instruction through structured support, hands-on practice, and digital literacy training. By merging creativity with pedagogy, it highlights the importance of integrating multimodal composing into teacher education programs in EFL instruction.